Finnish Coffee Addiction - Timo Myllyntaus (Deutsches Museum von Meisterwerken der Naturwissenschaft und Technik, 2022)
The consumption of coffee varies a lot nationally. One might search reasons for the differences from latitude, climate, culture, history, living standards, habits of everyday life and technology. Presumably, there is no single factor explaining these discrepancies.  Generally, the Nordic countries are among the biggest consumers of coffee per capita. Perhaps in those countries, there are reasons which encourage drinking coffee.   In 2017, an average Finn consumed 9.9 kg coffee per year. To put it in relative terms, an ordinary Finn drank 1,400 cups annually – that is three or five cups per day. Consequently, the Finns drink coffee more than any other nationality. The Norwegians, Swedes and Danes are near the top, as well. In the Nordic countries, cold climate, short daylight and long darkness in wintertime can be depressing, and people regard coffee as an invigorating and warming stimulant. In the 19th and 20th centuries, stoves and ovens were in winters heated several times a day. As a result, energy was frequently available for roasting coffee beans and brewing coffee. Especially in the countryside, firewoods were cheap. Moreover, these countries were sparsely populated, the industrialization of roasting and grounding of coffee started late, as well as coffee houses and restaurants were scarce. These factors encouraged roasting, grinding and brewing manually in households. Still nowadays, in these countries, most of the coffee is drunken at home. Drinking coffee became in a social habit and developed into a particular social culture, which was assimilated in national social institutions. Finland is the only country in the world that has nationwide, established coffee breaks in workplaces. According to the mutual agreements between the employers’ and employees’ unions, there must be two coffee breaks for employees on each workday of six hours or more.  As a result, the bunch of coffee drinking workmates is the core of social fabrics in Finnish working places.   In Finland, neither the industrialization of roasting and grinding coffee nor electric coffeemakers have disturbed the position of coffee culture. The Finns tend to choose coffeemakers by which they can brew large quantities of coffee at the same time.  Therefore, filtered coffee is prevalent in these countries. The paper claims that technology has not been the dominating factor in the development of the Finnish coffee culture. However, technology has facilitated changing trends in consumption habits. The adaptation of coffee making technology has made possible the development of the Finnish coffee culture and kept the consumption of coffee on the highest level in the world for decades.
Cosmos Coffee